Autumn light : season of fire and farewells - Iyer, Pico (Alfred A. Knopf, 2019)
"From one of our most astute observers of human nature, a far-reaching exploration of Japanese history and culture and a moving meditation on impermanence, mortality, and grief. For years, Pico Iyer has split his time between California and Nara, Japan, where he and his Japanese wife Hiroko have a small home. But when his father-in-law dies suddenly, calling him back to Japan earlier than expected, Iyer begins to grapple with the question we all have to live with: how to hold onto the things we love, even though we know that we and they are dying. In a country whose calendar is marked with occasions honoring the dead, this question is more urgent than anywhere else. Iyer leads us through the year following his father-in-law's death, introducing us to the people who populate his days: his ailing mother-in-law, who often forgets that her husband has died; his absent brother-in-law, who severed ties with his family years ago but to whom Hiroko still writes letters; and the men and women in his ping pong club, who, many years his senior, traverse their autumn years in different ways. And as the maple leaves begin to redden and the heat begins to soften, Iyer offers us a singular view of Japan, in the season that reminds us to take nothing for granted"--